International adoption: cultural socialization and identity development - Oesterle, Heidi (Kansas State University, 2009)
This report describes the role of cultural socialization in the ethnic identity formation of internationally adopted children. This report explores the process of integrating the child’s birth culture and the complexities that are involved in raising internationally adopted children. The theoretical frameworks of identity development and social construction will be used to provide a conceptual understanding of the process of ethnic identity development. This report will describe the use of Narrative Therapy and Child-centered Play Therapy to facilitate the process of identity development. Implications for clinical practice will be discussed.
Keywords: International adoption; Culture socialization; Identity theory and development; Child centered play therapy; Narrative Therapy; Social construction; Psychology, Behavioral (0384); Psychology, Clinical (0622); Psychology, Cognitive (0633); Psychology, Developmental (0620); Psychology, Social (0451); Social Work (0452); Sociology, Ethnic and Racial Studies (0631); Sociology, Individual and Family Studies (0628); Sociology, Public and Social Welfare (0630)